THE ROLE OF TECHNOLOGY IN FOSTERING A CIRCULAR ECONOMY: LITERATURE REVIEW AND PRACTICAL IMPLICATIONS - Loso Judijanto (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The purpose of this research is to examine the role of technology in supporting the implementation of a circular economy through a literature review and identify the practical implications of adopting these technologies. The circular economy offers an alternative approach to the traditional linear model, prioritising waste minimisation and resource use optimisation. This research highlights various information and communication technologies, such as big data, blockchain, and the Internet of Things (IoT), which have the potential to revolutionise resource management and improve the efficiency of industrial processes. In addition, innovations in product design and manufacturing, including 3D printing and the development of new environmentally-friendly materials, are discussed as key factors in ensuring longer and more sustainable product lifecycles. The study also reviews the challenges and opportunities in the application of these technologies, including the need for cross-sector collaboration and supportive regulations. The results show that technology integration in the circular economy not only contributes to environmental sustainability but also to increased economic value. Therefore, recommendations are provided to support the acceleration of technology adoption through education and public awareness initiatives.